2022
DOI: 10.14715/cmb/2021.67.5.11
|View full text |Cite
|
Sign up to set email alerts
|

MiR-494 Inhibits the Proliferation, Migration and Invasion of Cervical Cancer Cells by Regulating LETMD1

Abstract: LETMD1 is a differentially expressed gene selected by scientists from cervical cancer (CC) tissues by RT-PCR technology. It has been confirmed that LETMD1 is overexpressed in many human malignant tumors, so it can be used as an early diagnostic marker for malignant tumors and as a target for gene therapy. The purpose of this article is to further explore the effectiveness of miR-494 in inhibiting the proliferation, migration and invasion of CC cells by regulating LETMD1, selecting 40 cases of CC admitted to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In consequence, this complex regulation of different molecular targets could additionally explain the different, and in part opposing, functional changes in the investigated specific cancer models. Nevertheless, most recent reports dealing with miRs like miR-494 describe only one-to-one relationships between this miRNA and their individual target [ 25 , 26 , 107 , 108 , 109 , 110 , 111 ]. Certainly, our own present in vitro study can depict a small part of this regulatory network only.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, this complex regulation of different molecular targets could additionally explain the different, and in part opposing, functional changes in the investigated specific cancer models. Nevertheless, most recent reports dealing with miRs like miR-494 describe only one-to-one relationships between this miRNA and their individual target [ 25 , 26 , 107 , 108 , 109 , 110 , 111 ]. Certainly, our own present in vitro study can depict a small part of this regulatory network only.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that miR-494 is positively correlated with the survival time of CC patients ( Wen et al, 2022 ). When miR-494 was used to regulate LETMD1 expression, the proliferation, differentiation, and migration rates of HeLa cell lines increased slowly over 5 days, while the proportion of cancer cells decreased by 5%, the proportion of macrophages increased by 2%, and the proportion of dendritic cells increased by 3% after the expression of LETMD1 ( Wen et al, 2022 ). In an in vitro experiment, Yang et al found that downregulation of miR-494 expression inhibited CC cell proliferation and growth by regulating the expression of target gene PTEN , suggesting a potentially significant role of miR-494 in tumorigenesis and the development of CC, and introducing a new perspective for understanding of the molecular mechanisms underlying CC progression ( Yang et al, 2015 ).…”
Section: Mirna Interference With CC Developmentmentioning
confidence: 98%
“…Liu et al found a negative relationship between the overall survival of CC patients and miR-92a-3p, and observed that miR-92a-3p is able to promote CC stem cell proliferation, invasion, and cell cycle transition (Liu et al, 2021b). Another study found that miR-494 is positively correlated with the survival time of CC patients (Wen et al, 2022). When miR-494 was used to regulate LETMD1 expression, the proliferation, differentiation, and migration rates of HeLa cell lines increased slowly over 5 days, while the proportion of cancer cells decreased by 5%, the proportion of macrophages increased by 2%, and the proportion of dendritic cells increased by 3% after the expression of LETMD1 (Wen et al, 2022).…”
Section: The Role Of Mirnas In CC Diagnosis and Prognosismentioning
confidence: 99%
“…Studies have confirmed that miR‐494 plays a key role in apoptosis, proliferation, tumorigenesis, metastasis, and other processes. A number of studies have shown that miR‐494 is abnormally expressed in many diseases, among which miR‐494 was down‐regulated to varying degrees in cervical cancer, 12 spinal cord injury, 13 liver ischaemia/reperfusion injury, 14 and septicaemia‐induced myocardial injury. 15 On the contrary, miR‐494 expression was up‐regulated in bladder cancer, 16 diabetes‐induced myocardial injury, 17 Parkinson's disease, 18 and aging, 19 thus affecting the disease process.…”
Section: Introductionmentioning
confidence: 99%